Fabrication of carbon fiber tips for scanning probe microscopy - Villegas, Kevin (2012)
The Atomic Force Microscope (AFM) using a tuning fork as probe requires very sharp and light tips for obtaining topographic images with great resolution. On the other hand, Scanning Tunneling Microscopes (STM) needs sharp and conducting tips. Both requirements can be achieved using carbon fiber as the base material for the fabrication of the tips, with the additional advantage of being a material with a very low tendency to oxidize. In this work some initial results of the anodic dissolution technique are presented, which has permitted us to obtain the apex size of the tips in the nanometer scale. The electrochemical cell consists of the carbon fiber as the anode (7m diameter), a 2mm diameter Platinum ring as the cathode and Potassium Hydroxide as the electrolyte. A drop of the electrolyte is deposited on the Platinum ring and after that the carbon fiber is introduced into the drop. The polarization of the cell was obtained using a Potentiostat in Chrono-Amp mode, which permitted us to register Current vs. Time graphs for different values of potential applied. Correlations between the shape of the final tip and the molarity of the electrolyte, anodic potential, time for the anodic dissolution and the length of the carbon fiber beneath the air/electrolyte interface were found. Using Scanning Electron Microscopy, it was observed that tips with diameter lower than 70 nm can be obtained in a reproducible way.